Structure–Property Relationship of Membrane Materials in Water Treatment: Insights from Recent Literature - Nurul Fajri R. Tang; Andi Tessiwoja Tenri Ola; Rosdiana Yoku; Chrisaria Palungan; Dahlia Gladiola R. Manufandu; Vita Meylani; Rafsanjany Ramadani; Ryan Munandar (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2026)
The escalating global clean water crisis, driven by pollution and limited freshwater resources, has intensified the need for efficient and sustainable water treatment technologies. This review critically examines the structure–property relationships of membrane materials and their implications for water purification performance. Comparative analysis of recent studies reveals that hydrophilic membranes with controlled pore size (typically 0.01–0.1 µm) exhibit superior water flux (up to 65 L/m²·h·bar), higher pollutant rejection (>90%), and better fouling resistance than hydrophobic counterparts. Modifications involving nanoparticles (e.g., TiO₂, Fe₃O₄), composites (PES–DLC, PVDF–MOF), and biosurfactants have been shown to enhance hydrophilicity, optimize pore distribution, and extend operational stability. The review highlights the trade-off between permeability and selectivity, emphasizing the critical roles of pore size, contact angle, and surface chemistry in balancing efficiency and durability. It concludes that future membrane development should integrate nanostructure engineering, eco-friendly materials, and data-driven optimization to achieve adaptive, high-performance membranes for sustainable water purification.